Peran Habit Of Mind Budaya Sekolah Untuk Meningkatkan Karakter Tanggung Jawab Peserta Didik (Studi Deskriptif Kualitatif Di SMP Pasundan 3 Bandung) - Salsa Humaira (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Responsibility is an essential character value that should be developed through school culture. However, some students still demonstrate low responsibility, including poor discipline, late assignment submission, and limited concern for the school environment. Therefore, implementing Habit of Mind is considered important to foster responsible thinking and behavior. This study aims to describe the role of Habit of Mind in school culture to improve students’ responsibility character at SMP Pasundan 3 Bandung. The research employed a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation involving a Pancasila Education teacher, the Vice Principal for Student Affairs, and eighth-grade students. Data were analyzed through data reduction, data display, conclusion drawing, and triangulation. The findings indicate that the school’s culture integrates responsibility values through habituation programs and Pancasila Education learning. Although some obstacles remain, particularly students’ low awareness of responsibility, the school addresses them through personal guidance, teachers’ role modeling, collaboration with parents, and continuous evaluation. Therefore, the implementation of Habit of Mind plays an important role in improving students’ responsibility character.